Community Treatment of Drug Misuse : More Than Methadone. - Seivewright, Nicholas (Studies in social and community psychiatry., 2003)
This book draws on the author's direct clinical experience and makes use of international research findings to provide a comprehensive and highly practical guide to service provision and treatment for drug misuse. An essential resource for psychiatrists and other professionals involved in the management of drug misuse.